Hell - Gray, T; Gray, Tony J. (1996)
﻿ This thesis examines some major attempts made during the twentieth century to defend the doctrine of hell in the light of charges made against it. It aims to provide a survey of major statements of the doctrine, evaluate the coherence of the various arguments involved, and then determine what is the most adequate and coherent defence of the doctrine. The second and third chapters provide a backdrop to the rest of the thesis, detailing the traditional model of hell as presented in the works of St. Augustine and Jonathan Edwards, and then examining the modern reaction against hell as eternal retributive punishment. Chapter four addresses the question of whether Karl Barth was a universalist, and concludes that because he cannot logically avoid the charge of universalism, his theology is not able to provide an adequate defence of the doctrine of hell. The Roman Catholic theologians Hans Küng, Karl Rahner, and Hans Urs von Balthasar are examined in the fifth chapter. They provide a wealth of information on topics dealing with hell, and although hopeful that there will be a universal outcome in the eschaton, they defend the possibility of hell. The sixth chapter looks at the impact and influence of C.S.Lewis' work on hell, whilst the seventh addresses a recent debate concerning whether or not those in hell will cease to exist. Although the position known as conditional immortality may be viable, as a defence of hell in itself it is insufficient. The eighth and ninth chapters examine arguments used in the philosophy of religion. William Lane Craig and Thomas Talbott have debated the possibility of hell using the concept of Middle Knowledge. While Middle Knowledge is found wanting, this debate is particularly helpful in highlighting the issues involved in defending hell, and these are then considered in more detail in the ninth chapter which examines free will defences of hell. Finally, the conclusion argues that the most adequate and coherent defence of hell available to the modern mind rests itself on the principle of free will. When this defence addresses particular issues highlighted throughout the rest of the thesis, then a coherent defence of the doctrine of hell can be provided.